A Novel Technique of Impression Procedure in a Hemimaxillectomy Patient with Microstomia - Suryakant C. Deogade (Case Reports in Dentistry)
A restricted mouth opening in hemimaxillectomy patient can create a significant problem with the insertion and the removal of the obturator prosthesis. Even it poses a problem in impression making due to small oral opening. A modification of the standard impression procedure is often necessary to accomplish an acceptable impression in the fabrication of a successful prosthesis. Sectional trays are a good option for such patients. This paper describes a novel technique of impression procedure and a method of fabricating a sectional tray with the anterior and the posterior locking mechanism for a hemimaxillectomy patient with limited oral opening.